Effectiveness of capacity-building and technical assistance extended to young competition agencies (UN New YorkUS)
Assesses the assistance provided to young competition agencies, shows the progress achieved and the challenges that remain in providing effective capacity-building to interested agencies.
Keywords: COMPETITION POLICY